2015
DOI: 10.2337/dc15-0369
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Health Care Expenditure in U.S. Adults With Diabetes: 2002–2011

Abstract: OBJECTIVEDirect medical cost of diabetes in the U.S. has been estimated to be 2.3 times higher relative to individuals without diabetes. This study examines trends in health care expenditures by expenditure category in U.S. adults with diabetes between 2002 and 2011.RESEARCH DESIGN AND METHODSWe analyzed 10 years of data representing a weighted population of 189,013,514 U.S. adults aged ≥18 years from the Medical Expenditure Panel Survey. We used a novel two-part model to estimate adjusted mean and incremental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 31 publications
2
37
0
1
Order By: Relevance
“…Almost 70% of the health service costs associated with diabetes resulted from hospital admissions. Numerous studies report hospital admissions as the main driver of costs associated with diabetes and our findings highlight the need to provide effective interventions for the management of diabetes and related complications [22,23]. Increased risk of hospitalization in people with diabetes is attributable to macrovascular and microvascular complications [19,24].…”
Section: Discussionmentioning
confidence: 71%
“…Almost 70% of the health service costs associated with diabetes resulted from hospital admissions. Numerous studies report hospital admissions as the main driver of costs associated with diabetes and our findings highlight the need to provide effective interventions for the management of diabetes and related complications [22,23]. Increased risk of hospitalization in people with diabetes is attributable to macrovascular and microvascular complications [19,24].…”
Section: Discussionmentioning
confidence: 71%
“…Recent studies showed that socio demographic and binary indicators of disease are important covariates that affect medical expenditures 15 and that binary indicators of disease are more effective in accounting for disease burden. 1618 Covariates are age, sex, race/ethnicity, marital status, educational level, health insurance, metropolitan statistical area (MSA), region, poverty/income ratio (income level), calendar year, and comorbidities – diabetes, hypertension, cardiovascular diseases (CVD), emphysema, joint pain, arthritis and asthma.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from previous studies suggests that diabetes imposes a substantial economic burden on affected individuals, their families and communities, as well as on healthcare systems due to its growing prevalence and chronic nature [3][4][5][6] . A recent study estimated that among adults in China, the overall prevalence of diabetes was 10.9% 2 .…”
Section: Introductionmentioning
confidence: 99%